Emotional Intelligence and Engagement in Medicine Students: A Comparative Study in Three Countries - Hernández-Vargas, Clara Ivette; Llorens-Gumbau, Susana; Rodríguez-Sánchez, Alma María; Chambel, María Jose (Revista de Psicología, 2021)
This study aims to examine the relationship between emotional intelligence (IE) and engagement among medical students. Emotional intelligence was evaluated through the WLEIS scale and engagement by the UWES-9 in a sample of medical students (n = 522) from three countries: Mexico (National Autonomous University of Mexico, n = 27); Portugal (University of Lisbon, n = 232) and Spain (University of Extremadura, n = 163). Regression analysis revealed that students who have more emotional intelligence (specifically those who refer to using their emotions and direct them towards constructive activities and personal functioning) are also the students who presented greater engagement in their studies. Strategies should be implemented to develop emotional intelligence, as part of the contents in the medical training program in order to increase the engagement in students.